2017
DOI: 10.5603/fhc.a2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of proliferation markers and HSP90 gene expression as a predictor of pathological complete response in breast cancer neoadjuvant chemotherapy

Abstract: Introduction. Prediction of response to preoperative breast cancer chemotherapy may offer a substantial optimization of medical management of this disease. The most efficient prediction would be done a priori, before the start of chemotherapy and based on the biological features of patient and tumor. Numerous markers have been proposed but none of them has been applied as a routine. The role of MKI67 and HSP90 expression has been recently suggested to predict treatment sensitivity in HER2-positive breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
1
5
1
Order By: Relevance
“…The importance of proper selection increases with the growing number of treatment options for patients with breast cancer. The growing role of genomic approaches by complex or simpler predictors [24] is to be appreciated, but until they become more widespread in clinical practice, both tumour grade and surrogate St Gallen subtypes should be considered important features predicting the probability of pCR.…”
Section: Cdk1_210559_s_atmentioning
confidence: 99%
“…The importance of proper selection increases with the growing number of treatment options for patients with breast cancer. The growing role of genomic approaches by complex or simpler predictors [24] is to be appreciated, but until they become more widespread in clinical practice, both tumour grade and surrogate St Gallen subtypes should be considered important features predicting the probability of pCR.…”
Section: Cdk1_210559_s_atmentioning
confidence: 99%
“…A research illuminated that HSP90AA1 was overexpressed in BRAC and was correlated with shorter OS and aggressive clinicopathological features, including high clinical stage, large tumors, and lymph node involvement [ 37 ]. Jarzab et al found that low expression of HSP90AA1 and HSP90AB1 might indicate higher sensitivity to chemotherapy and higher probability of pathological complete response in BRAC patients [ 18 ]. Cheng et al found that high expression of HSP90AA1 and HSP90AB1 might be independent factors predicting poor prognosis of TNBC and ER+/HER2− patients, respectively, which was quite inconsistent with our findings [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic, prognostic, or predictive potentials of HSP90s genes had been partly reported previously [ 3 , 14 18 ]. However, the role of each HSP90s family member in the development and progression of every certain subtype of BRAC remains unknown.…”
Section: Introductionmentioning
confidence: 87%
“…80 Moreover, the ratio of CDK1 transcript to HSP90AA transcript was significant in the predictor of pCR for patients receiving NAC. 81 Besides, quinone oxidoreductase 1 (NQO1) was observed to rise in terms of the residual breast tumor tissues after NAC. 82…”
Section: Cyclin-dependent-kinase Expressionmentioning
confidence: 99%